2004
DOI: 10.1016/j.icesjms.2004.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Survival of reared and wild Atlantic salmon smolts: size matters more in bad years

Abstract: We compared the marine survival of Carlin-tagged wild and hatchery-reared Atlantic salmon smolts of the Simojoki river, northern Baltic Sea. All the reared and released smolts were the offspring of native spawners returning to the river. Reared smolts were adipose-fin-clipped and released from the hatchery several weeks before tagging. The wild and reared smolts were simultaneously caught and tagged at a smolt trap located at the Simojoki river mouth. The study was conducted in two years, 1991 and 1993, when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 15 publications
11
128
1
Order By: Relevance
“…When pond or hatchery reared, naive fish are released into wild habitats they encounter a variety of stressful situations and thus may be exposed to considerable mortality (Saloniemi et al, 2004). Contrary to our expectation, we did not find a direct relationship between the recapture rate and the stocking season in pikeperch.…”
Section: Discussioncontrasting
confidence: 99%
“…When pond or hatchery reared, naive fish are released into wild habitats they encounter a variety of stressful situations and thus may be exposed to considerable mortality (Saloniemi et al, 2004). Contrary to our expectation, we did not find a direct relationship between the recapture rate and the stocking season in pikeperch.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, rainbow trout removal through angling was comparable to that of farmed fish in other studies (21 to 52%; Uglem et al 2008, 2010, Lindberg et al 2009). Direct estimates of escapee survival are often difficult to derive, especially in the large systems where marine and freshwater aquaculture occurs, yet the present findings are consistent with the general observation that farmed fish have lower survival rates than their wild conspecifics (Einum & Fleming 2001, Saloniemi et al 2004.…”
Section: Discussionsupporting
confidence: 90%
“…In years of improved ocean productivity and exceptional recruitment, such as 2000 and 2001, selective mortality went undetected, as both large, fast-growing and small, slowgrowing individuals survived the ocean entry period. The selective mortality detected in 2005 is similar to cases presented by Holtby et al (1990), Blom et al (1994), Saloniemi et al (2004) and Cross et al (2008), who observed an increased benefit of larger size to other juvenile salmonids in low survival years. Poor conditions, driven by the late onset of upwelling in 2005 (Lindley et al 2009), may have created what Cushing (1990) described in the 'match-mismatch hypothesis'.…”
Section: Discussionsupporting
confidence: 80%